PELATIHAN PENGGUNAAN EJAAN YANG DISEMPURNAKAN DAN KALIMAT EFEKTIF PADA PENULISAN SURAT RESMI BAGI KURSUS BINTANG MULIA BATU BARA DESA PEMATANG RAMBAI KECAMATAN NIBUNG HANGUS KABUPATEN BATU BARA - Sri Rezki Maulina Azmi; Muthia Dewi; Akmal Akmal (STMIK Royal, 2019)
Abstrack: Indonesian for the Indonesian nation is the language of unity. Indonesian is also a communication tool for all Indonesian people. Therefore, Indonesian language learning is devoted to improving the ability of students to communicate using Indonesian language properly and correctly verbally or in writing. The community service activity entitled